UTILIZATION OF MANGROVE FRUIT (RHIZOPORA sp) AS AN ACTIVE INGREDIENT IN MAKING BODY SCRUB PREPARATION - Pangestika, Widya; Nusaibah, Nusaibah; Tresnawati, Intan Yulia (Aurelia Journal, 2025)
Body scrub is a cosmetic product that can remove dead skin cells, brighten the skin, and exfoliate dead skin cells in the stratum corneum. Body scrubs can be made from several types of plants, one of which is mangrove fruit. The purpose of this research is to create a body scrub that can moisturize the skin and contain high levels of antioxidants.This study was conducted on 4 treatments with the addition of mangrove (Rhizophora sp), namely F0 (Control), F1 (10% mangrove), F2 (15% mangrove) and F3 (20% mangrove). From the hedonic test conducted on 30 woman panelists aged 17-25 years, it was found that the sample that obtained the highest score was F1. Based on the results of the homogeneity test, it is known that all treatments in this study showed that the body scrub produced from this study was homogeneous. The results of the pH test showed that all body scrub preparations met the skin pH criteria, 4.5-7. Skin moisture after being smeared  for 5 days with body scrub increased every days.The results of the irritation test for each test sample showed negative results, The results of the antioxidant test (IC50) in F0 (Control) were 86664.78 mg/kg, in F1 (Addition of 10% mangrove) the IC50 value was 696.41 mg/kg, this shows that the addition of mangrove (Rhizophora sp) has a significant effect on the antioxidant activity of the body scrub preparation. This research proves that Rhizophora sp mangrove can be used as a body scrub preparation.